About the issue of classification of irregular and defective verbs - Muradyan, Viktorya (Bulletin of Yerevan University B: Philology, 2022)
The article studies the irregular and defective verbs of Grabar, the criteria of their classification, the similarities and differences between the classifications made by linguists, and a comparative study of these verbs. The examination of the opinions presented in the article is combined with the corresponding lists of irregular verbs, in which the bases of the irregularity and the principles of grouping the verbs are mentioned. One of the main issues under consideration is that different linguists include the same verb in different groups, presenting certain justifications. The general analysis is summarized and completed in the table at the end, where the differences in the existing approaches and verbs included in different groups are seen more clearly.